Trajectories of severe eating disorders through pregnancy and early motherhood - Sommerfeldt, Bente; Skårderud, Finn; Kvalem, Ingela Lundin; Gulliksen, Kjersti; Holte, Arne (Frontiers in Psychiatry, 2024)
Background: During pregnancy and early motherhood, risks of relapse and worsening are high for women with a history of eating disorders (EDs), as are adverse sequelae for their babies. However, systematic descriptions of the processes that these women undergo through pregnancy, birth, and early motherhood are lacking, as are good descriptions of the various trajectories these women follow through pregnancy and early motherhood. This study addresses both these knowledge gaps. Methods: We used a longitudinal research interview design, recruiting a non-clinical sample of 24 women with a history of severe EDs from routine pregnancy controls in five public, local, family health care centers in Norway. The participants were interviewed twice, first during pregnancy and then four to six months after delivery. Data were analyzed according to grounded theory. The focus was on modeling the trajectories of EDs through pregnancy, birth, and early motherhood. All the participants were diagnosed (DSM-5) using the Eating Disorder Examination and then completed the Eating Disorder Examination Questionnaire. Results: Five perceived trajectories through pregnancy and early motherhood were identified: “The mastering mother,” in which an ED pathology seems to be absent through pregnancy and early motherhood; “The inadequate mother,” in which the ED pathology worsens before pregnancy, through pregnancy, and early motherhood; “The overwhelmed mother,” in which the ED worsens during pregnancy and early motherhood; “The depressed mother,” in which the ED is put on hold during pregnancy, but worsens in early motherhood; and “The succeeding mother,” in which the ED worsens during pregnancy, but reduces in early motherhood. Discussion: ED trajectories through pregnancy and early motherhood vary greatly among women with a history of EDs. This may indicate different psychological dynamics through these phases. A model with five trajectories captures a large degree of the variation. The model may help clinicians’ preparedness when dealing with these patients.